Arte na formação pedagógica de professores do ensino superior - Linhares, Martha Maria Prata (2008)
This research investigates how art contributes to the pedagogic development of higher education professors. The theoretical basis is rooted in a proposal for teacher development, which has transformative learning as its fundamental characteristic. The investigation was carried out during participative observation of a post-graduate specialization course in University Teaching. The research was carried out under a qualitative approach of the ethnographic type. The registers of the teachers that took part in the course during the pedagogic development as well as after it were analyzed. The documents include registers of in-class meetings, and registers posted in the virtual learning environment used during the course. The data collected point to the fact that some characteristics were important in this process: the presentation of art; environments that promote dialogue; critical-reflection and transformative learning. It is possible to observe that art is an element that furthers the transformation of the real meanings of what we know and the meanings that we give to what we know. We concluded that to work with art is not only a way of creating presentations or products, it is a manner of creating our lives, broadening our consciences giving form to our characteristics, satisfying our search for meanings, establishing contact with others and sharing culture. We draw attention to the fact that the development of university professors does not mean a simple acquisition of knowledge, but a transformation of the whole person, the teacher. The introduction of art allowed for the development of environments in which differences were promoted and not excluded, it offered a great opportunity for understanding and development of social awareness, it strengthened imagination helping the docents in the interpretation of their practices and the transformation of the real meanings of what we know and the meanings that we give to what we know. Our analysis showed that inclusion of art in the higher education professor development is a new element that can provoke change and contribute to the pedagogic growth of university professors